Body Dissatisfaction, Perceptions of Competence, and Lesson Content in Physical Education. (10th July 2018) - Kerner, Charlotte; Haerens, Leen; Kirk, David
ABSTRACT: BACKGROUND: Significant proportions of young people experience body dissatisfaction, which has implications for psychological and physical well‐being. Lesson content and perceived competence may be important variables for the experience of body dissatisfaction, yet these have been underexplored in physical education. The aim of this cross‐sectional study is to identify the relationships between body dissatisfaction and perceptions of competence, and to explore whether body dissatisfaction depends on lesson content. METHODS: A paper‐and‐pencil questionnaire was completed by 446 (210 boys, 236 girls) 13‐ to 14‐year‐old pupils from 37 physical education classes. The questionnaire assessed body dissatisfaction and perceived competence in physical education. Lesson content was also recorded. Twenty‐nine of the classes were engaged in team activities, eg, ball games. Eight classes were engaged in individual activities, eg, fitness. RESULTS: Multilevel analysis identified a significant negative association between body dissatisfaction and perceptions of competence in physical education. Lesson content did not significantly predict variations in body dissatisfaction scores. CONCLUSIONS: Teachers should focus on enhancing pupils' perceptions of competence in physical education to support the development of body satisfaction.